2007
DOI: 10.1080/13691050600976650
|View full text |Cite
|
Sign up to set email alerts
|

Social organization of sexual‐economic networks and the persistence of HIV in a rural area in the USA

Abstract: In order to determine why high rates of HIV transmission have persisted in a rural area despite community-wide HIV prevention since the mid-1980s, qualitative information was collected about the contexts and social organization of risk behaviour for HIV transmission from residents of a southern Florida community with high HIV prevalence. Original data were collected during 1995-1997 using individual interviews, observations, focus groups, and print media. The research findings were recently reviewed by communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Empirical evidence from diverse trucking settings indicates that some North American regional and long-haul truckers engage in risk-laden sexual encounters with women and men that are often combined with illicit substances (Apostolopoulos et al, 2012, Stratford et al, 2007). Although the number of truckers who engage in these behaviors might be proportionally small, their interstate perpetual mobility and engagement in risky sexual behaviors pose risks to others.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence from diverse trucking settings indicates that some North American regional and long-haul truckers engage in risk-laden sexual encounters with women and men that are often combined with illicit substances (Apostolopoulos et al, 2012, Stratford et al, 2007). Although the number of truckers who engage in these behaviors might be proportionally small, their interstate perpetual mobility and engagement in risky sexual behaviors pose risks to others.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use, especially noninjecting cocaine use, is prevalent among African Americans in the rural South, putting rural African American substance users at even greater risk (Booth, Leukefeld, Falck, Wang, & Carlson, 2006; Chu & Selwyn, 2008; Farley, 2006; Fleming, Lansky, Lee, & Nakashima, 2006; Wright et al, 2007). HIV risk behaviors associated with cocaine use include having unprotected sex, using condoms inconsistently, having multiple concurrent sexual partners, having sex when using drugs, and trading sex for drugs or for survival needs (Adimora, Schoenbach, & Doherty, 2006; Fleming et al, 2006; Reif, Geonnotti, & Whetten, 2006; Stratford, Ellerbrock, & Chamblee, 2007; Wright et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Prior research in multiple world regions has shown that migrants often have limited HIV knowledge (4,5) and low perceptions of risk (6). Labor migrants may have multiple sexual partners (4,7,8), inconsistently use condoms, and have sex with commercial sex workers (6,9,10). Sexual harassment, abuse, or rape are commonly reported by female labor migrants (5,11).…”
Section: Introductionmentioning
confidence: 99%
“…Social factors that contribute to vulnerability include stresses associated with being away from spouses and other emotionally important persons in one’s home country for extended periods, as well as with lack of acculturation and assimilation in a destination country. Alcohol and drug use, unofficial status that prevents access to services, and absence of legal rights are common among labor migrants (7,9,10,14–16). …”
Section: Introductionmentioning
confidence: 99%